Congress of the Fundación Salud, Ciencia y Tecnología 2023 - Organizing Committee (SCT Proceedings in Interdisciplinary Insights and Innovations, 2023)
The Congress of the Fundación Salud, Ciencia y Tecnología 2023 brought together 123 papers by 348 authors from various countries, especially Spanish-speaking countries. Thematic highlights included medical risk management, community health, technological innovation, psychosocial factors and health equity. This research addresses contemporary challenges such as reproductive risk, primary care, the impact of technology on medicine and global disparities in access to services. The importance of preventive strategies, innovative interventions and a comprehensive approach to health was highlighted. The event fostered the exchange of interdisciplinary knowledge, promoting applicable solutions to improve the quality of life and the sustainability of health systems. This congress reaffirms the commitment of the scientific community to the generation of knowledge at the service of humanity.